Residual Feed Intake in Beef Cattle Is Associated With Differences in Hepatic mRNA Expression of Fatty Acid, Amino Acid, and Mitochondrial Energy Metabolism Genes - Taiwo, Godstime; Idowu, Modoluwamu D.; Wilson, Matthew; Pech-Cervantes, Andres; Estrada-Reyes, Zaira M.; Ogunade, Ibukun M. (Frontiers in Animal Science, 2022)
We evaluated the mRNA expression of genes involved in hepatic fatty acid, amino acid, and mitochondrial energy metabolism in crossbred beef steers with divergent low and high residual feed intake (RFI). Low-RFI beef steers (n = 8; RFI = - 1.93 kg/d) and high-RFI beef steers (n = 8; RFI = + 2.01kg/d) were selected from a group of 56 growing crossbred beef steers (average BW = 261 ± 18.5 kg) fed a high-forage total mixed ration after a 49-d performance testing period. At the end of the 49-d performance testing period, liver biopsies were collected from the low-RFI and high-RFI beef steers for RNA extraction and cDNA synthesis. The mRNA expression of 84 genes each related to fatty acid metabolism, amino acid metabolism, and mitochondrial energy metabolism were analyzed using pathway-focused PCR-based arrays. The mRNA expression of 8 genes (CRAT, SLC27A5, SLC27A2, ACSBG2, ACADL, ACADSB, ACAA1, and ACAA2) involved fatty acid transport and β-oxidation were upregulated (FC > 2.0, P < 0.05) in low-RFI, compared to high-RFI steers. Among those involved in amino acid metabolism, hepatic mRNA expression of a gene encoding for aminoadipate aminotransferase, an enzyme related to lysine degradation, was downregulated (FC = -5.45, P = 0.01) in low-RFI steers, whereas those of methionine adenosyltransferase I and aspartate aminotransferase 2, which both link amino acid and lipid metabolism, were upregulated (FC > 2, P < 0.05). Two mitochondrial energy metabolism genes (UQCRC1 and ATP5G1) involved in ATP synthesis via oxidative phosphorylation were upregulated (FC > 2; P < 0.05) in low-RFI beef steers, compared to high-RFI beef steers. The results of this study demonstrated that low-RFI beef steers exhibit upregulation of molecular mechanisms related to fatty acid transport, fatty acid β-oxidation, and mitochondrial ATP synthesis, which suggest that low-RFI beef steers have enhanced metabolic capacity to maximize capture of energy and nutrients from feeds consumed.